Prognostic relevance of disseminated tumour cells from the bone marrow of early stage breast cancer patients: results from a large single-centre analysis - Hartkopf, Andreas; Taran, Florin-Andrei; Wallwiener, Markus; Hahn, Markus; Becker, Sven; Solomayer, Erich-Franz; Brucker, Sara Y.; Fehm, Tanja N.; Wallwiener, Diethelm (European journal of cancer, 2014)
Background - This is the largest single-centre study to determine the prognostic relevance of disseminated tumour cells (DTCs) from the bone marrow (BM) of stage I-III breast cancer patients. Additionally, we aimed to analyse the impact of DTC detection on adjuvant bisphosphonate (BP) treatment efficacy. - Methods - BM aspirates were collected during primary surgery for early breast cancer (EBC; T1-4, N0-2, M0) at Tuebingen University, Germany, between January 2001 and January 2013. DTCs were identified by immunocytochemistry (pancytokeratin antibody A45/B-B3) and cytomorphology. We retrospectively estimated the influence of DTC detection and BP treatment on disease-free survival (DFS) and overall survival (OS) using univariate (log-rank test) and multivariate (cox regression) analysis. - Findings - BM aspirates were available from 3141 patients. In 803 (26%) of these, DTCs were detectable. As compared to DTC-negative patients, DTC-positive patients more frequently had larger tumors (p<0.001), lymph node involvement (p<0.001), hormonal receptor positive tumours (p<0.001) and HER2-positive tumours (p=0.048). DTC-positive patients were at an increased risk of relapse (hazard ratio (HR) 1.74, 95% confidence interval (CI) 1.34-2.25, p<0.001) and death (HR 1.44 95% CI 1.13-1.86, p=0.004). In the multivariate analysis DTCs were an independent predictor of DSF and OS. Additionally, BP treatment had no significant influence on DFS or OS in DTC-negative patients, while it was significantly associated with increased DFS (p<0.001) and OS (p=0.006) in DTC-positive patients. - Interpretation - These data confirm the clinical validity of DTCs from the BM for prognostication of early breast cancer patients. Further studies are warranted to determine whether DTCs are predictive for adjuvant treatment efficacy using bisphosphonates.